Wear-resistant anti-icing insulating material as well as preparation method and application thereof

By using insulating materials composed of polyurethane and heptadecyl trimethoxysilane modified silica, the short circuit problems caused by the formation of ice and snow and surface filth under low temperature conditions are solved, and excellent insulation, hydrophobic and sparse are achieved. Oil performance, with anti-ice, anti-wet flash and anti-fouling flash effects.

CN119432221AInactive Publication Date: 2025-02-14SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411088343.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119432221A_ABST
    Figure CN119432221A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant anti-icing insulating material as well as a preparation method and application thereof. The wear-resistant anti-icing insulating material disclosed by the invention is prepared from polyurethane and silicon dioxide modified by heptadecafluorodecyl trimethoxy silane. The preparation method of the wear-resistant anti-icing insulating material comprises the following steps: 1) preparing polyurethane; and 2) dispersing polyurethane, heptadecafluorodecyl trimethoxysilane modified silicon dioxide, a surface modifier and a photoinitiator in a hydrophobic solvent to prepare a dispersion liquid, then coating the surface of a substrate with the dispersion liquid, and then carrying out drying and ultraviolet curing to obtain the wear-resistant anti-icing insulating material. The wear-resistant anti-icing insulating material disclosed by the invention is excellent in insulating property, hydrophobic and oleophobic, has anti-icing, anti-wet-flashover and anti-pollution-flashover effects when being used as a protective layer of an insulator, and is suitable for large-scale industrial generation and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating materials, and in particular to a wear-resistant and ice-resistant insulating material and a preparation method and application thereof. Background Art

[0002] Insulators are devices installed between conductors of different potentials or between conductors and grounded components, which can withstand voltage and mechanical stress. They play an important role in overhead transmission lines. Insulators are easily affected by low temperature weather and are prone to snow and ice on the surface (especially when the distance between insulators is small). When the temperature rises above zero degrees Celsius, the melting of ice and snow will form ice water slides, which can easily cause short circuits in transmission lines, which will eventually not only affect the operation of the entire transmission line, but also pose a great safety hazard. In addition, when the surface of the insulator is attached and moistened by dirt during use, it is easy to cause flashover, which will also affect the normal operation of the transmission line.

[0003] Therefore, it is of great significance to develop an insulating material with excellent insulation performance, hydrophobicity and oleophobicity, and anti-icing / anti-humidity flashover / anti-pollution flashover effects as a protective layer for insulators. Summary of the invention

[0004] The object of the present invention is to provide a wear-resistant and ice-proof insulating material and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is:

[0006] A wear-resistant and ice-proof insulating material comprises polyurethane and silicon dioxide modified by heptadecafluorodecyltrimethoxysilane.

[0007] Preferably, the heptadecafluorodecyltrimethoxysilane-modified silica is prepared by a preparation method comprising the following steps: dispersing silica in a solvent, adding heptadecafluorodecyltrimethoxysilane to react, and then separating and drying the product to obtain heptadecafluorodecyltrimethoxysilane-modified silica.

[0008] Preferably, the weight ratio of the silicon dioxide to heptadecafluorodecyltrimethoxysilane is 1:0.04-0.06.

[0009] Preferably, the reaction is carried out at room temperature for 1 h to 5 h.

[0010] Preferably, the weight ratio of the polyurethane to the silica modified with heptadecafluorodecyltrimethoxysilane is 1:0.3-1.2.

[0011] More preferably, the weight ratio of the polyurethane to the silica modified with heptadecafluorodecyltrimethoxysilane is 1:0.8-1.2.

[0012] A method for preparing the wear-resistant and ice-proof insulating material as described above comprises the following steps:

[0013] 1) mixing isophorone diisocyanate, 2-hydroxyethyl acrylate and a catalyst for condensation reaction, and then adding a chain extender for chain extension reaction to obtain polyurethane;

[0014] 2) Dispersing polyurethane, silica modified by heptadecafluorodecyltrimethoxysilane, a surface modifier and a photoinitiator in a hydrophobic solvent to prepare a dispersion, coating the dispersion on the surface of a substrate, and then drying and UV curing to obtain a wear-resistant and anti-icing insulating material.

[0015] Preferably, in step 1), the weight ratio of isophorone diisocyanate to 2-hydroxyethyl acrylate is 1:0.4-0.6.

[0016] Preferably, the catalyst in step 1) is an organotin catalyst.

[0017] Further preferably, the catalyst in step 1) is dibutyltin dilaurate.

[0018] Preferably, the chain extender in step 1) is at least one of trimethylolpropane and triethylolpropane.

[0019] Preferably, the surface modifier in step 2) is tetraethyl silicate.

[0020] Preferably, the photoinitiator in step 2) is at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, benzophenone, diacetophenone, 2,4-dihydroxybenzophenone, α,α-dimethoxy-α-phenylacetophenone, α,α-diethoxyacetophenone, α-hydroxyalkyl phenone, and α-aminoalkyl phenone.

[0021] Preferably, the hydrophobic solvent in step 2) is at least one of cyclopentyl methyl ether, acetone, benzene, toluene and tetrahydrofuran.

[0022] Preferably, the UV curing time in step 2) is 10 min to 30 min.

[0023] An insulator, the surface of which is covered with the above-mentioned wear-resistant and ice-proof insulating material.

[0024] The beneficial effects of the present invention are as follows: the wear-resistant and anti-icing insulating material of the present invention has excellent insulating properties, is hydrophobic and oleophobic, and has anti-icing, anti-wet flashover, and anti-pollution flashover effects when used as a protective layer of an insulator, and is suitable for large-scale industrial production and application.

[0025] Specifically:

[0026] The present invention utilizes polyurethane to form a polymer cross-linked network with high toughness and high strength, and connects silica modified with heptadecafluorodecyltrimethoxysilane to the polymer cross-linked network through chemical bonds (the surface of the insulating material is covered with a large amount of silica modified with heptadecafluorodecyltrimethoxysilane). On the premise of ensuring that the insulating material has excellent electrical insulation properties, the hydrophobicity and oleophobicity of the insulating material are significantly improved, and ultimately the insulating material is endowed with excellent anti-icing, anti-humidity flashover and anti-pollution flashover effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The infrared spectra of the wear-resistant and ice-resistant insulating material of Example 4 and the insulating material of Comparative Example 2 are shown.

[0028] Figure 2 This is the nuclear magnetic resonance hydrogen spectrum of the wear-resistant and ice-proof insulating material of Example 4.

[0029] Figure 3 This is a graph showing the water contact angle test results of the wear-resistant and ice-resistant insulating materials of Examples 1 to 4 and the insulating materials of Comparative Examples 1 to 2.

[0030] Figure 4 This is a graph showing the wet flash resistance test results of the wear-resistant and ice-resistant insulating material of Example 4.

[0031] Figure 5 The SEM images of the wear-resistant and anti-icing insulating materials of Examples 1 to 4 and the insulating materials of Comparative Examples 1 to 2 and the surface element distribution map of the wear-resistant and anti-icing insulating material of Example 4 are shown.

[0032] Figure 6 This is a graph showing the self-cleaning performance test results of the wear-resistant and ice-resistant insulating material of Example 4.

[0033] Figure 7 This is a graph showing the anti-icing performance test results of the wear-resistant anti-icing insulating material of Example 4.

[0034] Figure 8 It is a test result diagram of the pressure resistance performance of the wear-resistant and ice-proof insulating materials of Examples 1 to 4 and the insulating materials of Comparative Examples 1 to 2.

[0035] Fig. 9 This is a graph showing the test results of the water contact angle and rolling angle of the wear-resistant and ice-proof insulating material of Example 4 on substrate surfaces of different materials. DETAILED DESCRIPTION

[0036] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0037] The preparation method of the heptadecafluorodecyltrimethoxysilane-modified silica in Examples 1 to 4 and Comparative Example 2 is as follows: 5 g of silica is dispersed in a mixed solvent consisting of 100 mL of ethanol and 1 mL of deionized water at room temperature by stirring, and then 0.25 g of heptadecafluorodecyltrimethoxysilane is added and stirred for 2 h. The mixture is filtered and the solid is dried in an oven at 60° C. to obtain heptadecafluorodecyltrimethoxysilane-modified silica.

[0038] Embodiment 1:

[0039] A wear-resistant and ice-proof insulating material, the preparation method of which is as follows:

[0040] 1) 4.44 g of isophorone diisocyanate and 2.32 g of 2-hydroxyethyl acrylate were mixed and stirred at room temperature for 30 min, and then 1 drop of dibutyltin dilaurate was added and the stirring was continued for 4.5 h, and then 0.894 g of trimethylolpropane was added and stirred until the reaction solution solidified to obtain polyurethane;

[0041] 2) The polyurethane was dissolved in 80 mL of acetone under stirring at room temperature, and then 7.6 mL of cyclopentyl methyl ether, 16 mL of tetraethyl silicate and 0.08 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were added and stirred evenly, and then 3.36 g of silica modified with heptadecafluorodecyltrimethoxysilane was added and stirred evenly to prepare a dispersion, and then the dispersion was coated on the surface of the aluminum sheet, and then dried at room temperature for 1 min, and then irradiated with ultraviolet light with a wavelength of 365 nm for 15 min to obtain a wear-resistant and anti-icing insulating material.

[0042] Embodiment 2:

[0043] A wear-resistant and ice-resistant insulating material is prepared in the same manner as in Example 1 except that the amount of silicon dioxide modified with heptadecafluorodecyltrimethoxysilane in step 2) is adjusted from 3.36 g to 5.04 g.

[0044] Embodiment 3:

[0045] A wear-resistant and ice-resistant insulating material is prepared in the same manner as in Example 1 except that the amount of silicon dioxide modified with heptadecafluorodecyltrimethoxysilane in step 2) is adjusted from 3.36 g to 6.73 g.

[0046] Embodiment 4:

[0047] A wear-resistant and ice-resistant insulating material is prepared in the same manner as in Example 1 except that the amount of silicon dioxide modified with heptadecafluorodecyltrimethoxysilane in step 2) is adjusted from 3.36 g to 8.41 g.

[0048] Comparative Example 1:

[0049] An insulating material, which is completely the same as Example 1 except that no silica modified with heptadecafluorodecyltrimethoxysilane is added in step 2) during preparation.

[0050] Comparative Example 2:

[0051] An insulating material is prepared in the same manner as in Example 1 except that the amount of silicon dioxide modified with heptadecafluorodecyltrimethoxysilane in step 2) is adjusted from 3.36 g to 1.68 g.

[0052] Performance Test:

[0053] 1) The infrared spectra of the wear-resistant and ice-proof insulating material of Example 4 and the insulating material of Comparative Example 2 are as follows: Figure 1 shown.

[0054] Depend on Figure 1 It can be seen that the wear-resistant and anti-icing insulating material of Example 4 has more functional groups such as -CF2- and -CF3 than the insulating material of Comparative Example 2, which indicates that the wear-resistant and anti-icing insulating material of Example 4 contains fluorine element.

[0055] 2) The nuclear magnetic resonance hydrogen spectrum of the wear-resistant and ice-proof insulating material of Example 4 is as follows Figure 2 shown.

[0056] Depend on Figure 2 It can be seen that the wear-resistant and ice-proof insulating material of Example 4 does contain polyurethane segments.

[0057] 3) The water contact angle test results of the wear-resistant and ice-resistant insulating materials of Examples 1 to 4 and the insulating materials of Comparative Examples 1 to 2 are as follows: Figure 3 (Aluminum plate as control).

[0058] Depend on Figure 3 It can be seen that the greater the amount of silica modified with heptadecafluorodecyltrimethoxysilane added to the insulating material, the better its hydrophobic property.

[0059] 4) The wear-resistant and ice-proof insulating material of Example 4 (coated on the surface of the epoxy resin board with a thickness of 20 μm) was tested for its wet flash resistance. The specific test process is as follows: the test sample is tilted 15°, and electrodes are clamped at both ends. Deionized water is then dripped on the surface of the test sample at a rate of 1 drop per second, and the discharge voltage between the two electrodes is measured. The test results are as follows: Figure 4 (Epoxy resin board was used as control and was marked as ER).

[0060] Depend on Figure 4It can be seen that the average wet flash strength of the wear-resistant and ice-proof insulating material of Example 4 is 19.65 kV / cm, which is much higher than 10.87 kV / cm of the epoxy resin board.

[0061] 5) The scanning electron microscope (SEM) images of the wear-resistant and ice-resistant insulating materials of Examples 1 to 4 and the insulating materials of Comparative Examples 1 to 2 and the surface element distribution map of the wear-resistant and ice-resistant insulating material of Example 4 are as follows: Figure 5 (a is the SEM image of the insulating material of comparative example 1, b is the SEM image of the insulating material of comparative example 2, c is the SEM image of the wear-resistant and anti-icing insulating material of embodiment 1, d is the SEM image of the wear-resistant and anti-icing insulating material of embodiment 2, e is the SEM image of the wear-resistant and anti-icing insulating material of embodiment 3, f is the SEM image of the wear-resistant and anti-icing insulating material of embodiment 4, and g is the surface element distribution map of the wear-resistant and anti-icing insulating material of embodiment 4).

[0062] Depend on Figure 5 It can be seen that the greater the amount of silica modified with heptadecafluorodecyltrimethoxysilane added to the insulating material, the higher the surface roughness of the insulating material.

[0063] 6) The wear-resistant and ice-proof insulating material of Example 4 (coated on the surface of the glass plate with a thickness of 20 μm) was tested for its self-cleaning performance. The specific test process was as follows: the test sample was tilted 10°, dust was selected as the pollutant and placed on the surface of the test sample, and then methylene blue dyed water was dropped on the surface of the pollutant to observe the movement law of the water droplets to remove the pollutants on the surface of the test sample. The test results are shown in FIG. Figure 6 (The glass plate is used as a control; the left column in the figure is Example 4, and the right column is the control group).

[0064] Depend on Figure 6 It can be seen that the wear-resistant and ice-proof insulating material of Example 4 has excellent self-cleaning performance.

[0065] 7) The anti-icing performance of the wear-resistant anti-icing insulating material of Example 4 (coated on the surface of the glass plate with a thickness of 20 μm) was tested. The specific test process was as follows: the test sample was attached to the semiconductor plate (the glass plate was in contact with the semiconductor plate), the temperature of the semiconductor plate was adjusted to -20°C, the test sample was tilted 30°, and then methylene blue dyed water was dropped on the surface of the test sample to observe the icing process of the water drop on the surface of the test sample. The test results are as follows: Figure 7 (The glass plate is used as a control; the left sample in each small picture in the figure is the control group, and the right sample is Example 4; the small pictures from left to right in the figure are the ice coating process of the test samples).

[0066] Depend on Figure 7 It can be seen that the wear-resistant anti-icing insulating material of Example 4 has excellent anti-icing performance.

[0067] 8) The wear-resistant and ice-proof insulating materials of Examples 1 to 4 and the insulating materials of Comparative Examples 1 to 2 (coated on the surface of the glass plate with a thickness of 20 μm) were subjected to a withstand voltage performance test. The specific test process is as follows: the voltage rise rate is controlled to be 500 V / s to perform a breakdown resistance test on the test sample until the test sample is broken down. The obtained breakdown resistance test results are as follows: Figure 8 shown.

[0068] Depend on Figure 8 It can be seen that the wear-resistant and anti-icing insulating materials of Examples 1 to 4 have good pressure resistance performance, among which the wear-resistant and anti-icing insulating material of Example 4 has the best pressure resistance performance, which is significantly better than the insulating materials of Comparative Examples 1 to 2.

[0069] 9) The water contact angle and rolling angle test results of the wear-resistant and ice-resistant insulating material of Example 4 on the substrate surfaces of different materials (aluminum, epoxy resin and silicone rubber) (refer to the operation of Example 4 to prepare the wear-resistant and ice-resistant insulating material on the substrate surfaces of different materials) are as follows: Fig. 9 shown.

[0070] Depend on Fig. 9 It can be seen that the wear-resistant and ice-proof insulating material of Example 4 has excellent hydrophobic properties on the surfaces of substrates of different materials, indicating that it has good universality.

[0071] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A wear-resistant and ice-proof insulating material, characterized in that: The composition includes polyurethane and silica modified with heptadecafluorodecyltrimethoxysilane.

2. The wear-resistant and ice-proof insulating material according to claim 1, characterized in that: The heptadecafluorodecyltrimethoxysilane-modified silica is prepared by a preparation method comprising the following steps: dispersing silica in a solvent, adding heptadecafluorodecyltrimethoxysilane for reaction, and separating and drying the product to obtain heptadecafluorodecyltrimethoxysilane-modified silica.

3. The wear-resistant and ice-proof insulating material according to claim 2, characterized in that: The weight ratio of the silicon dioxide to heptadecafluorodecyltrimethoxysilane is 1:0.04-0.

06.

4. The wear-resistant and ice-proof insulating material according to claim 2, characterized in that: The reaction is carried out at room temperature and the reaction time is 1 h to 5 h.

5. The wear-resistant and ice-proof insulating material according to any one of claims 1 to 4, characterized in that: The weight ratio of the polyurethane to the silica modified by heptadecafluorodecyltrimethoxysilane is 1:0.3-1.

2.

6. A method for preparing the wear-resistant and ice-proof insulating material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) mixing isophorone diisocyanate, 2-hydroxyethyl acrylate and a catalyst for condensation reaction, and then adding a chain extender for chain extension reaction to obtain polyurethane; 2) Dispersing polyurethane, silica modified by heptadecafluorodecyltrimethoxysilane, a surface modifier and a photoinitiator in a hydrophobic solvent to prepare a dispersion, coating the dispersion on the surface of a substrate, and then drying and UV curing to obtain a wear-resistant and anti-icing insulating material.

7. The preparation method according to claim 6, characterized in that: In step 1), the weight ratio of isophorone diisocyanate to 2-hydroxyethyl acrylate is 1:0.4-0.

6.

8. The preparation method according to claim 6 or 7, characterized in that: The catalyst in step 1) is an organotin catalyst; Step 1) The chain extender is at least one of trimethylolpropane and triethylolpropane.

9. The preparation method according to claim 6 or 7, characterized in that: The surface modifier in step 2) is tetraethyl silicate; the photoinitiator in step 2) is at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, benzophenone, diacetophenone, 2,4-dihydroxybenzophenone, α,α-dimethoxy-α-phenylacetophenone, α,α-diethoxyacetophenone, α-hydroxyalkyl phenone, and α-aminoalkyl phenone.

10. An insulator, characterized in that: The surface is covered with the wear-resistant and ice-proof insulating material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of carbon fiber surface modification anti-oxidation composite coating

    CN110318253A

  • Photocuring anti-doodling coating with self-healing function and preparation method and application thereof

    CN112812685A